2022
DOI: 10.1186/s12889-022-14266-7
|View full text |Cite
|
Sign up to set email alerts
|

Type, density, and healthiness of food-outlets in a university foodscape: a geographical mapping and characterisation of food resources in a Ghanaian university campus

Abstract: Introduction Food environments are viewed as the interface where individuals interact with the wider food system to procure and/or consume food. Institutional food environment characteristics have been associated with health outcomes including obesity and nutrition-related non-communicable diseases (NR-NCDs) in studies from high-income countries. The objectives of this study were (1) to map and characterise the food-outlets within a Ghanaian university campus; and (2) to assess the healthiness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…The most frequently used assessment tool across the studies included in this review was the NEMS, with eight versions used across various settings (e.g., campus dining, vending). For example, four studies used NEMS for restaurants to assess on-campus eateries [6,14,38,47]. An in-depth summary of the most frequently used assessment tools is described in the following sections.…”
Section: Food Environment Tools and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most frequently used assessment tool across the studies included in this review was the NEMS, with eight versions used across various settings (e.g., campus dining, vending). For example, four studies used NEMS for restaurants to assess on-campus eateries [6,14,38,47]. An in-depth summary of the most frequently used assessment tools is described in the following sections.…”
Section: Food Environment Tools and Methodsmentioning
confidence: 99%
“…A summary of the included study characteristics, including assessment type, focus, and scope, is shown in Table 1. Eighteen studies were conducted in the United States [6][7][8][9][10]13,17,18,24,[30][31][32][33][34][38][39][40][41], four in Australia [15,28,42,43], three in Brazil [14,27,44], two in Canada [12,45], and one in Egypt [46], Ghana [47], Italy [48], Lebanon [49], New Zealand [50], Norway [51], Spain [11], South Africa [52], and United Arab Emirates [29]. Thirteen studies compared multiple higher education institutions [6][7][8][9]13,15,28,29,38,43,[49]…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, geographical mapping is mainly used to visualize national and sub-national health data [26]. In public health, geographical mapping is sometimes used collaboratively [27][28][29] or thematically [30], but without really superimposing healthcare needs and resources integrating a care pathway. On the one hand, cartographic interaction and collaboration, representing the dialogue between a human and a map, provides auxiliary background knowledge and auxiliary map-reading tools to facilitate the transfer of geographical knowledge to the public [29].…”
Section: What Place Can Thermal Spa Therapies Take In the Care Pathwa...mentioning
confidence: 99%